Appointment, powers, duties and liabilities of receivers / Hasbi Hasan - Hasan, Hasbi (Faculty of Law, 1987)
Companies may be rescued by formal and informal compromises or arrangements with creditors. Constituent. business may be preserved as going concerns by receivere or liquidators through various means including hiving-down. The failure or business and tte dissolution of companies is an unevitable .part of entrepreneurial activity. Thus one sees large companies such as Rolls Royce, International Harvester, and Carrian going to the wall, and recently in Singapore Lee Wah Cane, Lamipak, Pan Electric and assorted retailers, manufacturers and construction companies. It may seem odd to regard receivership as a means of avoidi.ng liquidation of the company. It is, after all, procedure for the creditor to take control of the dehtors' property which forms the security. When would a receiver play C'. part in a corporate rescue? Loan agreements where outstandings are secured by fixed or floating charges commonly contain provisions which allow the creditor to take control of the property by appointing a receiver who exercises powers granted to him under the loan agreement or related security documents. These powers generally permit the receiver to protect or realize the security or assets of the company.